78 Human Tenocyte Metabolism Under Pathological And Physiological Loading Conditions. (5th September 2014) - Patel, Dharmesh; Bryant, Stephanie; Riley, Graham; Jones, Eleanor; Screen, Hazel
Abstract : Introduction: Tendinopathies are common, debilitating tendon disorders, seen among both athletes and non-athletes. Due to the unclear aetiology of tendinopathy, treatment is often generalised, and efficacy limited. Changes in mechanical and cellular interactions after microdamage are thought to be key in developing tendinopathy (Arnoczky et al ., 2007). Therefore understanding how the cell strain environment modulates matrix turnover and catabolism is essential. A unique fibre composite system has been developed for this purpose. It mimics the unique tenocyte environment by encapsulating cell-coated polyethylene glycol (PEG)-RGD rods within a PEG matrix, using UV light initiated polymerisation. By recapitulating the specific, tightly controlled strain conditions, seen by tenocytes in situ, multiple post-analysis techniques such gene expression can be explored. Materials and Methods: PEG-RGD rods of two stiffness were made (20% and 60% PEG), and soaked for 10 or 60 min prior to encapsulation to generate four different shear:tension ratios for cells. Rods were seeded with either healthy or diseased human tenocytes (obtained following surgery with ethical permissions) prior to encapsulation; 12 composites for each strain condition. The local strain environment was characterised by straining composites whilst visualising rod extension and shear with brightfield microscopy and cell deformation with confocal microscopy. The cell response to strain was also characterised, applying 5% cyclic strain (1Hz) to samples for 24hrs, in custom-built chambers maintained in an incubator. Gene expression across the groups was compared via RT-qPCR. Results: Tenocytes successfully attach to rods in all composite conditions and remain viable. Altering the materials chemistry of rods and surrounding PEG, adjusted the extent of rod strain in relation to the applied gross strain (Figure 1 ), creating a spectrum of local cell strain conditions, spanning physiological and pathological conditions. Preliminary results confirm that strain applied to the construct does result in cell deformation. Gene expression analysis has shown that human tenocytes respond to brief handling when encapsulated in composites, particularly with an up-regulation of MMP1, and it takes 24 h for gene expression to stabilise. Cells also respond to the range of shear:tension strain ratios, with MMP1 and COL1A1 differentially regulated by varying shear strains and rod stiffness. Discussion/ Conclusion: This novel fibre composite material provides the first system able to investigate tenocyte mechanotransduction and physiological and pathological levels of cell shear and tension. Current experiments have begun identifying the cell strain conditions associated with catabolic and anabolic matrix turnover, providing an exciting avenue for further understanding tendinopathy. Data suggests that the shear-strain ratio experienced by cells could be an important factor regulating their behaviour. Acknowledgments: Dharmesh Patel is supported by an Arthritis Research UK Studentship. Reference: Arnoczky, et al . Int J Exp Pathol, 2007;88:217–26